2014
DOI: 10.1371/journal.pone.0093083
|View full text |Cite
|
Sign up to set email alerts
|

Putting the C Back into the ABCs: A Multi-Year, Multi-Region Investigation of Condom Use by Ugandan Youths 2003–2010

Abstract: A major strategy for preventing transmission of HIV and other STIs is the consistent use of condoms during sexual intercourse. Condom use among youths is particularly important to reduce the number of new cases and the national prevalence. Condom use has been often promoted by the Uganda National AIDS Commission. Although a number of studies have established an association between condom use at one’s sexual debut and future condom use, few studies have explored this association over time, and whether the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In a meta-analytical review of studies, exposure to condom promotion messages in HIV prevention strategies was found to have great potential to reduce partners among those trading in sex, especially when delivered as part of a comprehensive risk reduction program ( 38 ). A study among Ugandan adolescents also indicated that condom promotion messages in early adolescence results in establishing a safe and lasting behavior pattern in young people ( 39 ). Hence, there is a need to emphasize the development of comprehensive risk reduction strategies that not only include components aimed at reducing multiple and concurrent sexual partners but also include negotiation and communication skills aimed at consistent condom use among young people.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analytical review of studies, exposure to condom promotion messages in HIV prevention strategies was found to have great potential to reduce partners among those trading in sex, especially when delivered as part of a comprehensive risk reduction program ( 38 ). A study among Ugandan adolescents also indicated that condom promotion messages in early adolescence results in establishing a safe and lasting behavior pattern in young people ( 39 ). Hence, there is a need to emphasize the development of comprehensive risk reduction strategies that not only include components aimed at reducing multiple and concurrent sexual partners but also include negotiation and communication skills aimed at consistent condom use among young people.…”
Section: Discussionmentioning
confidence: 99%
“…Kampala); Table 1 shows how the data were distributed between four Uganda regions. Similar regional classifications have been used in previous studies [ 23 , 26 , 37 ]. The donor selected the districts surveyed each year; hence there is some variation in the geographical regions from one year to another ( S1 Table ).…”
Section: Methodsmentioning
confidence: 98%
“…This study uses secondary data sources collected using the Lot Quality Assurance Sampling method (LQAS), which has been used extensively to monitor and evaluate community-based programmes in Uganda and elsewhere. These data result from the roll out of LQAS as a national health sector monitoring system in Uganda, which has been supported by USAID since 2009 ( http://www.starelqas.ug ) [ 26 ]. Uganda used standard LQAS procedures [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports consistently indicate the greatest burden of HIV/AIDS being borne by least developed (and mostly poor) countries while sub-Sahara Africa (SSA) has remained the most affected region [ 2 ]. Targeting to implement health interventions to areas where the HIV/AIDS epidemic is much more concentrated is greatly recommended, and this includes identification of the groups at most risk of the infections and who are most vulnerable of the epidemic so that they can use appropriate preventive such as condoms and treatment products such as antiretroviral (ARV) drugs, coupled with proper health education and counseling services [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%